Development and validation of HPLC method for simultaneous determination of Gliclazide and Enalapril maleate in tablet dosage form - Al Mahmud, Md Abdullah; Bhadra, Subrata; Haque, Afroza; Al Mamun, Md Elias; Haider, Syed Shabbir (Dhaka University Journal of Pharmaceutical Sciences, 2015)
This paper describes a simple, sensitive and selective high performance liquid chromatographic (HPLC) method for the separation and determination of gliclazide (GLI) and enalapril (ENA) maleate simultaneously in tablet dosage forms. The chromatographic separation was performed on an ODS column (250 mm × 4.6 mm i.d., 5 ?m particle size) at 40 ± 0.5°C, with a mobile phase composed of phosphate buffer (pH 4.4), acetonitrile and methanol in the ratio of 45:40:15, (v/v/v). The flow rate was maintained at 1.5 ml/min, injected volume was 20 ?l and detection wavelength was 217 nm. The method was validated according to ICH Q2 (R1) guidelines and found to be linear over a range of 40-120 ?g/ml (R2 = 0.991) and 2.5-7.5 ?g/ml (R2 = 0.998) for gliclazide and enalapril maleate, respectively. The proposed method was applied successfully for the assay of these two drugs in their combined inhouse developed tablet formulations and could be applicable for routine quality control analysis. DOI: http://dx.doi.org/10.3329/dujps.v13i1.21859 Dhaka Univ. J. Pharm. Sci. 13(1): 51-56, 2014 (June)